Official account of the military operations in China, 1900-1901 - Norie, E.M.W (Victorian war series, 1995)
Commences with the rise of the Boxer Secret society, and the outbreak of hostilities against foreigners, extends to military operations to free the Foreign Legations in Peking. Covers the conclusion of peace and the withdrawal of the allied forces from China. Contains a selection of maps.